Anatomical variability of the frontal sinuses and their application in forensic identification - Nambiar, P.; Naidu, M.D.K.; Subramaniam, K. (1999)
The uniqueness of anatomical structures and their variations provides the basis for forensic identification of unknown deceased persons. Similar to fingerprints, each frontal sinus is so distinctive and unique that the chances of two individuals having the same morphology of the frontal sinuses is extremely remote. Radiographs, especially the occipitomental view commonly used in the assessment of paranasal pathology, provide excellent records of these sinuses. The case illustrated here is an application of the frontal sinus identification of a victim in a mass disaster. Clin. Anat. 12:16-19, 1999. (C) 1999 Wiley-Liss, Inc.